Extraction Behaviour of Dioctylamine and Tricaprylamine Toward Uranium and Some of the Metal Ins - Al- Taweel, H.H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
The extraction behaviour of a secondary amine (Dioctylamine) and a combination of secondary amine and tertiary amine (Tricapryl amine) toward some of the metal ions were investigated. Two types of diluents were applied, namely, mesitylene and treated Kerosene fraction. The extractability of dioctylamine and different combinations of tertiary amine and secondary amine toward uranium were investigated. The distribution coefficients and the separataion factors of uranium from the metal ions were calculated.